A technique for intraoperative creation of patient-specific titanium mesh implants. Issue 2 (May 2015) - Sunderland, Ian Rp; Edwards, Glenn; Mainprize, James; Antonyshyn, Oleh
Prefabricated, patient-specific alloplastic implants for cranioplasty reduce surgical complexity, decrease operative times, minimize exposure and risk of contamination, and have resulted in improved aesthetic results. However, in creating a prefabricated custom implant using a patient's computed tomography data, a stable, unalterable defect must be clearly defined before surgery. In the event that an intraoperative modification of an exiting skull defect is required, or in cases of tumour resection in which the size of the skull defect is unknown preoperatively, these prefabricated implants cannot be used. The ideal method for alloplastic cranioplasty would enable cost-effective creation of a patient-specific implant with the capacity for intraoperative modification. The present article describes a novel technique of cranioplasty that uses a patient's computed tomography data to create a custom forming tool (ie, mold), enabling intraoperative creation of a patient-specific titanium mesh implant. The utility of these implants in creating a custom reconstructive solution in cases in which the size of the skull defect is unknown preoperatively will be demonstrated using two case presentations.